Anatomical and ultrasound correlation of the superficial branch of the radial nerve. Issue 6 (3rd November 2014) - Meng, Stefan; Tinhofer, Ines; Weninger, Wolfgang J.; Grisold, Wolfgang
ABSTRACT Introduction: This anatomical study evaluates the role and correlation of ultrasound (US) with anatomy in depicting the superficial branch of the radial nerve (SBRN) and to evaluate the feasibility of US guided perineural infiltration as a potential therapeutic option in Wartenberg syndrome. Methods: Twenty‐one arms from 11 non‐embalmed cadavers were examined with US. Under US guidance perineural injection with ink was performed proximal to the site where the SBRN perforates the forearm fascia. The distribution of ink around the nerve was evaluated with dissection. Results: US allowed the distinction of the SBRN segments and their relation to the fascia. In all cases, the subfascial segment was stained. In only 57% the subfascially applied ink also reached the subcutaneous compartment. Conclusions: With US it is possible to examine and differentiate all segments of the SBRN. US guidance can be used for perineural injection of all relevant segments. Muscle Nerve 50: 939–942, 2014